Využití Competitive Intelligence pro predikci budoucích kroků konkurenta - Antošová, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Tato diplomová práce představuje možnosti využití Competitive Intelligence pro predikci možných kroků konkurenta v konkurenčním prostředí.

This Master´s Thesis introduces options of using Comptitive Intelligence to predict future actions of Competitor in Competitive environment.
Use of Competitive Intelligence to Predict the Future Actions of Competitors
Keywords: Competitive Intelligence; konkurence; benchmarking; konkurenční prostředí; analýza; metoda; konkurenční výhoda.; Competitive Intelligence; Competition; Benchmarking; Competitive environment; Analysis; Method; Competitive advantage.